Pengaruh Karakteristik Pekerjaan dan Knowledge Sharing terhadap Kepuasaan Kerja dengan Komitmen Organisasional sebagai Variabel Mediasi - Ardelia Ernestine; Wahju Wulandari; Mulyono Mulyono (Institut Nalanda, 2024)
The purpose of this study was to determine the effect of job characteristics and knowledge sharing on job satisfaction with organisational commitment as a mediating variable (study on employees of Bank CIMB Niaga South Jakarta Branch Office). The population in this study are all employees and employees who work at Bank CIMB Niaga South Jakarta Branch Office. The sampling method in this study used the Slovin formula and obtained a sample size of 55 respondents. Data is processed through Smart Partial Least Square (PLS) software. The results showed that better job characteristics can increase job satisfaction and organisational commitment. Similar to job characteristics, better knowledge sharing can also increase job satisfaction and organisational commitment. Meanwhile, stronger organisational commitment is also proven to affect job satisfaction. Organisational commitment acts as a mediator of the effect of job characteristics and knowledge sharing on job satisfaction of employees of Bank CIMB Niaga South Jakarta Branch Office.